Effect Of Application of Rich Media Advertising on Purchase Decisions: Study of Travel Companies - M. Liga Suryadana; Rizki Nurul Nugraha (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
This study aims to determine the effect of the application of the Rich Media Advertising dimension to purchasing decisions. The population in this study were service users who had purchased packages in the past three years. This study involved 100 service users as research subjects taken randomly. This study uses research instruments in the form of questionnaires and interview guidelines. Both instruments validated before being applied to the study sample. Furthermore, the data obtained were analyzed using Path analysis. The results of the study indicate that: (1) There is a Significant Effect of Streaming Audio on purchasing decisions. (2) There is a Significant Effect of Streaming Video on purchasing decisions. (3) There is a Significant Effect of the Applets That Allow User Interaction on purchasing decisions. (4) There is a Significant Effect of Special Effect that has a significant effect on purchasing decisions. Based on these findings it can be concluded that Rich Media Advertising has a significant influence on purchasing decisions with a percentage of influence of 51.4%.